Effects of electrical discharge machining (EDM) jet flushing setting on the machining of tool steel workpiece - Hasan, Muda (2009)
Electrical Discharge Machining (EDM) is one of the most accurate manufacturing process for creating complex or simple shape and geometries within parts and assemblies. EDM works by eroding material in path of electrical discharges that form an arc between an electrode tool and the work piece. The objective of this thesis project is to determine effect of EDM jet flushing setting on the machining of tool steel workpiece. The most important parameters of EDM are the material removal rate (MRR) and surface roughness (Ra). The non-electrical factors are considered in this experiment where the electrical factor has been fixed. In this thesis the influence of electrode material, flushing, electrode dimension and depth of cut on EDM performance is discussed. The analysis of the influence of these factors was carried out by adopting a complete factorial experiment. Graphite and Copper are used as electrode to machine the workpiece. Flushing is used in EDM to remove the eroded particle from the gap for efficient cutting. There are two level of flushing setting, for low level flushing is not used and at high level flushing is used. Electrode dimension for low level is 10 mm and high level is 30 mm. the factor for depth of cut is 10 mm at low and 20 mm at high level. The dielectric fluid is used kerosene. The effects of jet flushing was analyzed and discussed. The result had proved that flushing is very important to influence MRR and Ra result.